The economywide effects of reducing food loss and waste in developing countries - Aragie, Emerta A.; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2023)
One of the Sustainable Development Goals (SDGs) is reducing food loss and waste (FLW) across all stages of food value chains, including the on-farm production, the off-farm postharvest, processing, and distribution, and the household consumption stages. We employ general equilibrium models for Bangladesh, Kenya, and Nigeria to assess the economywide implications of reducing FLW at different stages of value chains. Halving FLW results in GDP increases of between 1.1 and 2 percent, with up to 13 million people lifted out of poverty across the three countries. Diets also improve – especially in Kenya and Nigeria – due to greater availability and lower prices of healthy foods such as fruits and vegetables. Although most of the gains originate from reducing FLW in the on-farm production stage, strong intersectoral linkages mean around 30 percent of measured GDP gains are realized in non-agricultural sectors. Reducing waste at the final consumption stage has small negative impacts on GDP as households purchase less food without reducing their food intake. We conclude that the significant economywide gains provide a justification for adopting FLW reduction strategies, although costing the policy and investment options needed to reduce FLW is an important area for future research.